An Appraisal of Missions in the Calvary Grace Bible Church, Oyo, Nigeria - Falaye, T. A. (NIU Journal of Social Sciences; Vol 6 No 2 (2020): KIU Journal of Social Sciences, Vol. 6 No. 2, June 2020, 2020)
This study appraises Missionary activities in the Calvary Grace Bible Church, Inc in the light of Paul Missiology. The main focus of this study was on the methods and impacts of both ministries in the contemporary world. It was established that although methods can vary with time and place but the principles remain the same. Some mission strategies that were not known to Paul were seen adopted in the Calvary Grace Bible Church. But both missions are seen addressing issues as occasions allow it. It was therefore recommended that we must must do as much as possible to care for the physical needs of our members and especially the needy ones in our communityand also use our stewardship of "influence or connection" to find jobs for numerous Christian that are around us. Keywords : Missions, Church, Nigeria